90.1k views
0 votes
How do I do this because I don’t remember how

How do I do this because I don’t remember how-example-1
User Melquan
by
6.4k points

1 Answer

5 votes

Answer: h = 3

Step-by-step explanation: The first step is to collect like terms and simplify as much as possible.

We have

2h³ - 11 = 43

Add 11 to both sides of the equation

2h³ - 11 + 11 = 43 + 11

2h³ = 54

Divide both sides of the equation by 2

h³ = 27

Add the cube root sign to both sides of the equation

h = 3

(That is, the cube root/third root of 27 equals 3)

User Miranda
by
4.4k points